DAMPAK UTANG PEMERINTAH PUSAT TERHADAP KEBERLANJUTAN FISKAL INDONESIA PERIODE 1998-2017 - Rastri Paramita; Jesly Yuriaty Panjaitan (Pusat Kajian Anggaran, 2018)
Debt is a part of the government's fiscal policy which also being the part of the financial management policy. The purpose of this study is to analyze the impact of the Government Debt on fiscal sustainability during 1998-2017 and the impact of debt ratio, inflation, real interest rate dan real growth on primary balance. The study uses both qualitative and quantitative methods. The quantitative methods use accounting method and VECM method. The qualitative method uses debt ratio, primary balance ratio and debt service to income ratio. The result shows a fiscal unsustainability occurred in the periode 1998 – 2017 and there was a positive impact of debt ratio, inflation, real interest rate and real growth on primary balance. Government therefore needs to make an innovation in creating new income, to improve the quality of disbursement and to manage the debt more prudent.